ARTIFICIAL NEURAL NETWORKS IN REDUCING THE ENERGY CONSUMPTION OF EXISTING ELECTRICAL SYSTEMS IN TEXTILE ENTERPRISES - Kuchkarova , Dilnoza Toptiyevna (Educational Research in Universal Sciences, 2023)
In this case, artificial neural networks serve as the optimal solution for reducing the energy consumption of existing electrical systems in textile enterprises. The analysis of existing electric drives in the enterprise showed that in order to implement control with speed modes, it was considered necessary to change the speed affecting the product by adjusting the rotation speed of the drive, to combine artificial neural networks based on a mathematical model and to create the effect of giving the desired speed based on the constant product volume.